Application of HBOCs electrophoretic method to detect a new blood substitute derived from the giant extracellular haemoglobin of lugworm. Issue 11 (13th January 2017) - Marchand, A.; Crepin, N.; Roulland, I.; Semence, F.; Domergue, V.; Zal, F.; Polard, V.; Coquerel, A.
Abstract : Manipulation of blood and blood components is prohibited in sports by the World Anti‐Doping Agency (WADA). This includes the use of blood substitutes to increase oxygen transport, like haemoglobin‐based oxygen carriers (HBOCs), which are compounds derived from haemoglobin. Despite their medical interest, the first generation of HBOCs had serious adverse effects and was abandoned. However, new studies are now exploiting the properties of marine worm haemoglobins, which circulate as giant extracellular complexes with high oxygen‐binding capacities. HEMOXYCarrier® (HC), developed by Hemarina, is one of the most advanced and promising HBOCs, and HC may become a tempting doping tool for athletes in the future. Here, HC detection in plasma/serum was evaluated with the method used to detect the first HBOCs, based on electrophoresis and heme peroxidase properties. An HC‐derived product was identified in human plasma up to 72 h after in vitro incubation at 37 °C. HC degradation also induced methemalbumin formation. After injecting HC at the effective dose of 200 mg/kg into mice, the HC‐derived product was detected only for a few hours and no accumulation of methemalbumin was observed. Due to this limited detection window in vivo, measuring specific worm globin degradation products by mass spectrometry might be an alternative for future anti‐doping analyses. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The aim of this work was to test the capacity of detection of a new kind of haemoglobin‐based oxygen carrier (HBOC) issued from a marine worm. The electrophoretic method used for detection of the first‐generation HBOC was applied. The highlights of this work are: HEMOXYCarrier ® produced by HEMARINA is a future blood substitute with doping potential. Detection of this product in plasma/serum using the electrophoretic HBOC method is applicable but limited in vivo to a few hours. Research of peptides specific of worm globins in blood or urine could increase the window of detection.